Mangiferin attenuates bleomycin‐induced pulmonary fibrosis in mice through inhibiting TLR4/p65 and TGF‐β1/Smad2/3 pathway. (7th March 2019) - Jia, Li; Sun, Ping; Gao, Hui; Shen, Jie; Gao, Yuan; Meng, Cheng; Fu, Shidong; Yao, Huijuan; Zhang, Gong
Abstract: Objectives: Investigating the antipulmonary fibrosis effect of mangiferin from Mangifera indica and the possible molecular mechanism. Methods: In vivo, bleomycin (BLM)‐induced pulmonary fibrosis experimental model was used for evaluating antipulmonary fibrosis effect of mangiferin. Histopathologic examination and collagen deposition were investigated by HE and Masson staining as well as detecting the content of hydroxyproline. The expression of transforming growth factor‐β1 (TGF‐β1), α‐smooth muscle actin (α‐SMA), TLR4 and p‐P65 in lung tissue was analysed through immunofluorescence. Leucocytes and inflammatory cytokines including IL‐1β, IL‐6, TNF‐α and MCP‐1 in bronchoalveolar lavage fluid were detected by cell counting and enzyme‐linked immunosorbent assay. In vitro, TGF‐β1‐induced A549 epithelial–mesenchymal transition (EMT) cell model was used for investigating the possible molecular mechanism. Reactive oxygen species (ROS) generation was detected by DCFH‐DA assay. Expression of all proteins was examined by Western blot. Key findings: Oral administration of mangiferin could attenuate the severity of BLM‐induced pulmonary fibrosis through increasing the survival rate, improving histopathological lesion and body weight loss as well as decreasing pulmonary index visibly. Pulmonary hydroxyproline content, TGF‐β1, and α‐SMA levels were reduced significantly. The molecular mechanism of mangiferin for inhibiting pulmonary fibrosis is that it could obviously inhibit the occurrence of inflammation and the secretion of inflammatory cytokine through inhibiting activation of TLR4 and phosphorylation of p65. Meanwhile, EMT process was suppressed obviously by mangiferin through blocking the phosphorylation of Smad2/3 and reducing MMP‐9 expression. Besides, mangiferin could significantly inhibit the process of oxidant stress through downregulating the intracellular ROS generation. Conclusions: Mangiferin attenuates BLM‐induced pulmonary fibrosis in mice through inhibiting TLR4/p65 and TGF‐β1/Smad2/3 pathway.